2016
DOI: 10.21303/2461-4262.2016.00075
|View full text |Cite
|
Sign up to set email alerts
|

Features of Changes of Structure and Adhesive Properties for Acrylic Adhesives Under the Influence of the Filler

Abstract: The research results of the effect of concentration of injected mineral filler on change in adhesion strength of acrylic adhesive composition to the metal substrate are given in the article. The adhesive composition was prepared based on pre-compounded reaction system: the stabilized monomer – methyl methacrylate and polymer modifier – sterol copolymer with methyl methacrylate with followed filling and polymerization in the presence of a redox system. It is shown that the mobilization to resource preservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…of nanoparticles causes TiO 2 particles to agglomerate and spread unevenly. where these results are in line with research reported by previous researchers [30], besides, the concentration of filler material can increase the adhesion strength of the material [37,38]. The improvement of mechanical properties of cassava starch/PVA-TiO 2 nanocomposite films was in line with previous studies using a variety of fillers on starch/glycerol/Li composite films [30], and starch-sisal fiber [39].…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…of nanoparticles causes TiO 2 particles to agglomerate and spread unevenly. where these results are in line with research reported by previous researchers [30], besides, the concentration of filler material can increase the adhesion strength of the material [37,38]. The improvement of mechanical properties of cassava starch/PVA-TiO 2 nanocomposite films was in line with previous studies using a variety of fillers on starch/glycerol/Li composite films [30], and starch-sisal fiber [39].…”
Section: Mechanical Propertiessupporting
confidence: 92%